Pemeliharaan Benih Ikan Baung (Mystus Nemurus C.V) Dengan Sistem Bioflok Pada Sistem Resirkulasi Akuaponik - Tiya Sari Harahap; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from July to August 2014, for 35 days in Breeding Laboratory Unit of Fisheries Faculty and Marine Sciences, University of Riau Pekanbaru. The aims of the research was to investigate rearing of river catfish (Mystus nemurus C.V) with biofloc system in aquaponic recirculation system. The method used was experiment with 3 treatments and 3 replications. The treatments were P1 = 20 ml/L of probiotic bacteria inoculant, P2 = 25 ml/L of probiotic bacterial inoculant, and P3 = 30 ml/L of probiotic bacteria inoculant. The best treatment was achieved by P3 with absolute growth weights (3.79 g), absolute growth length (6.10 cm), daily growth rate (6.54%) and survival rate 90%. The best water quality parameters recorded during in the research period was achieved by P3 ammonia (NH3) 0.33-0.72 mg/L, nitrit (NO2) 0.07-0.55 mg/L, nitrat (NO3) 0.13-1.23 mg/L, temperature 27-30 0C, pH 5-6, dissolved oxygen (DO) 3-4.5 mg/L and (CO2) 7.99-11.98 mg/L.Keywords: River catfish seed (Mystus nemurus) biofloc, Aquaponic recirculation